Windfallen ebook - Moyes, Jojo (2013)
From the #1 New York Times bestselling author of Me Before You, the basis for the major motion picture, comes a breathtaking drama of two women whose lives entwine through a lovely English seaside house. For Lottie Swift, Arcadia has always been magical. The breathtaking art deco house perched above the shoreline of the well-ordered village of Merham seems to stand still throughout the years. It has never changed, not really, but Lottie's fate and fortune have been inextricably linked with that of the beautiful house, and it will forever be fixed in her mind as a symbol of adventure, youth, and of loves lost and gained. Even as her life—and the house—fall into disrepair. Years later another young woman comes to Merham. A designer hired to make over the now-empty Arcadia, Daisy Parsons seeks a new beginning, as Lottie once did. Fleeing a broken relationship and now facing being a single mother, Daisy finds refuge in the house, and something more—a love she thought she would never know again and a friendship unlike any she's experienced before.